(untitled) (ZOO-Journal, 2019)
Present study surveyed fish diseases in ponds of Begnas area in Pokhara Valley, Nepal. The fishes were collected with the help of the local fishermen and were examined under compound microscope in the laboratory of Pokhara Fisheries Research Centre, Begnas. Two fish diseases, Tail rot and Arugulosis were reported of which later was dominant.